Extraction of natural dyes from Alpinia blepharocalyx K. Schum. for dyeing of silk fabric. (3rd October 2012) - Wang, Chunxia; Xu, Changhai; Tian, Anli; Fu, Shaohai; Wang, Chaoxia
Abstract : Natural dyes were extracted from the leaves and stems of Alpinia blepharocalyx K. Schum. Analysis of the designed experiment revealed that extraction at a plant/water ratio of 1:20 could reach an optimal production of natural dyes when extraction was performed at 80 °C, for 4 h, under 20 min ultrasound, in the presence of 10 g/l sodium hydroxide, and with two extractions. The extracted natural dyes were applied to the dyeing of silk fabrics using different methods, including or excluding a mordant. It was found that mordants had a significant effect on the colour of dyed silk fabrics. The silk fabric dyed with the pre‐mordant method using potassium aluminium sulphate as a mordant showed a bright yellow with a higher colour strength. The optimal dyeing conditions were reached when the extracted natural dyes were pre‐mordanted with 10 g/l potassium aluminium sulphate at pH 6, and for a 20 min dyeing time.